Being asked to respond. The ethical position and challenge of Person-Centered Therapy and the “necessary and sufficient conditions of being person-centered” (Polis (Santiago), 2018)
What does it really mean to be person-centered? Is it a (‘postmodern’) question of what you like and what you believe? Where are the limits? Is it possible to indicate a core? And if so, what is it? Is it possible to combine orientations, to integrate methods and add techniques? Is there actually a ‘Beyond Carl Rogers’? What are the prospects of the development and influence of what once was regarded a radical paradigm? Where is it going to and what will be its future? What is its place and challenge in the realm of psychotherapy and counseling? A clear stance is argued that it is indeed possible to name the necessary and sufficient conditions of being person-centered. The question of being person-centered ultimately turns out to be an ethical one.
Keywords: person; being person-centered; psychotherapy and ethics